THE RELATIONSHIP BETWEEN DEPRESSION, ANXIETY AND ACUTE CORONARY SYNDROME - Made Widiyanti (Universitas Udayana, 2013)
Depression and anxiety occur at high prevalence in patients with acute coronary syndrome. Studies have shown that depression is also a significant risk factor for new cases of heart disease and can increase the morbidity and mortality of heart disease. Despite the high prevalence and have serious effects, the symptoms of depression and anxiety are often unrecognized and untreared in mostly patients with acute coronary syndrome and some of the symptoms during months. The standard therapy for this disorder is safe, well tolerated and can be effective for this population; in fact, the selective serotonin reuptake inhibitors can improve the outcome of the disorder of the heart. The purpose of this paper would adding a better sense about the effect of the combination of depression and anxiety, as well as with prospective research about the influence of therapy on the results of the heart disorder.